2016
DOI: 10.1007/s10455-016-9495-3
|View full text |Cite
|
Sign up to set email alerts
|

Balanced metrics on the Fock–Bargmann–Hartogs domains

Abstract: The Fock-Bargmann-Hartogs domain D n,m (µ) (µ > 0) in C n+m is defined by the inequality w 2 < e −µ z 2 , where (z, w) ∈ C n × C m , which is an unbounded non-hyperbolic domain in C n+m . This paper introduces a Kähler metric αgThe purpose of this paper is twofold. Firstly, we obtain an explicit formula for the Bergman kernel of the weighted Hilbert space of square integrable holomorphic functions on (D n,m (µ), g(µ; ν)) with the weight exp{−αΦ} for α > 0. Secondly, using the explicit expression of the Bergman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…For the case of non-compact manifolds, Loi-Mossa in [28] have shown that a bounded homogeneous domain admits a regular quantization. For the nonhomogeneous setting, we give the existence of regular quantizations on some Hartogs domains in [6] and [18].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For the case of non-compact manifolds, Loi-Mossa in [28] have shown that a bounded homogeneous domain admits a regular quantization. For the nonhomogeneous setting, we give the existence of regular quantizations on some Hartogs domains in [6] and [18].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Finally, we describe what we need about the 1-parameter family of Fock-Bargmann-Hartogs domains, referring the reader to [1] and reference therein for details and further results. For any value of µ > 0, a Fock-Bargmann-Hartogs domain D n,m (µ) is a strongly pseudoconvex, nonhomogeneous unbounded domains in C n+m with smooth real-analytic boundary, given by:…”
Section: Notice That It Is An Open Question If the Same Statement Holmentioning
confidence: 99%
“…In [1], E. Bi, Z. Feng and Z. Tu prove that when n = 1 and ν = − 1 m+1 , the metric ω(µ; ν) is infinite projectively induced whenever it is rescaled by a big enough constant. More precisely they prove the following: Recall that a balanced Kähler metric is a particular projectively induced metric such that the immersion map is defined by a orthonormal basis of a weighted Hilbert space (see e.g.…”
Section: Notice That It Is An Open Question If the Same Statement Holmentioning
confidence: 99%
“…11671306). c 2020 Australian Mathematical Publishing Association Inc. [2] L p regularity of the weighted Bergman projection 283…”
mentioning
confidence: 99%
“…Thus, A 2 (Ω, η) is a subspace of holomorphic functions in L 2 (Ω, η). From [18], if η is continuous and never vanishes inside Ω, then A p (Ω, η) is a closed subspace of L 2 (Ω, η) and there is an orthogonal projection, called the weighted Bergman projection,…”
mentioning
confidence: 99%